2003
DOI: 10.1590/s1413-86702003000400006
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HbsAg, anti-HBc and anti-HCV in Southern Brazil, 1999-2001

Abstract: The prevalence of infection by the hepatitis B (HBV) and C (HCV) viruses varies among geographical regions. We evaluated 263,795 blood donor samples collected from 1999-2001 in various cities in the state of Santa Catarina to determine the prevalence of HbsAg, anti-HBc and anti-HCV markers. The markers were analyzed by immunoenzymatic tests, as determined by the Ministry of Health, and the data were obtained from blood banks and from ANVISA (the Brazilian National Agency for Sanitary Vigilance). There was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
44
4
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 33 publications
(29 reference statements)
9
44
4
3
Order By: Relevance
“…The prevalence of positive serology for viral hepatitis found in this study is similar to those reported previously for Brazil by other authors (HBsAg: 0.14-0.78%, anti-HBc: 2.05-13.44%, anti-HCV: 0.34-1.14%) [46][47][48] . The prevalence of hepatitis B markers in Brazil varies greatly by region.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of positive serology for viral hepatitis found in this study is similar to those reported previously for Brazil by other authors (HBsAg: 0.14-0.78%, anti-HBc: 2.05-13.44%, anti-HCV: 0.34-1.14%) [46][47][48] . The prevalence of hepatitis B markers in Brazil varies greatly by region.…”
Section: Discussionsupporting
confidence: 91%
“…In Brazil, higher HIV prevalence rates among men and those with lower educational levels were reported for both the general population 15 and blood donors 10 , including in the capital of Florianópolis compared with other regions of the State of Santa Catarina 1,16 . The present study showed that the City of Criciúma had the highest HIV and HCV risk among blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been conducted on hepatitis B and C, especially on blood banks 6,7,8,9,10,11,12 , there are few studies carried out among the general population 13,14,15 , and due to territorial extension, and cultural and economic differences, the distribution of these diseases in the country differs among regions 16 .…”
Section: Introductionmentioning
confidence: 99%